Religiosity in the Novel of â€œGaruda di Dadakuâ€ by Salman Aristo: A Semiotic Analysis and Its Relevance to High School Literature Education - Asni Sri Hidayati; Mukti Widayati; Nurnaningsih Nurnaningsih (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This research carries the main objective of uncovering the religious values contained in the novel â€œGaruda di Dadakuâ€ by Salman Aristo and exploring its relevance in the context of literary education in secondary schools. Through a semiotic approach, this study aims to identify and analyze the various religious themes implied in the literary work, including aspects such as faith, Sharia, and morality. In an educational context, these values have great potential to be integrated into the literature curriculum in secondary schools as part of the effort to teach students Islamic character, morals, and teachings. The results of the research analysis highlight key elements such as Aqidah, Sharia, justice, responsibility, and effort contained in the novel. The findings not only provide deep insights into the religious messages conveyed through such literary works, but also provide a solid basis for developing relevant and effective learning strategies in the classroom. By using the novel as teaching material, literature teachers can facilitate in-depth discussions on the religious values found in the story, providing students with opportunities to reflect on and internalize the moral messages conveyed. Thus, this study emphasizes the importance of using literature as a tool to discuss and instill religious values in students. As a relevant and effective resource in literature learning in secondary schools, the novel â€œGaruda di Dadakuâ€ not only provides a deep reading experience, but also opens the door for deep reflection on life values and religious teachings. Thus, this study makes an important contribution to curriculum development and literature learning practices centered on understanding religious values, semiotics, and students' literary experiences